Newton's First Law of motion is not real (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Newton's first law of motion is well recognized theory for physics. But my attempt is to obtain a contradiction to Newton's first law of motion. It may be a challenge to the physics world. Consider an object that has carried to the empty space that has not effected by any external force. Then apply an external force with some heat. At time T=0, the force applies to the object. Then, after some time duration, we take away the force. By considering the behaviors of fundamental building particles of the object, we obtain a contradiction to the Newton's first law of motion. There are large number of applications of Newton's first law of motion. Specifically, for the space-based experiments, this new concept plays a major role.